2009
DOI: 10.4103/0970-0218.45373
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Goiter in rural area of Belgaum district, Karnataka

Abstract: Background:To determine the prevalence of goiter and to study the factors influencing goiter among people of the rural community in Karnataka state, a community based study. Setting and Study Design: A cross sectional study was carried out to find out the prevalence of goiter in a rural community of Belgaum district. The study was conducted by house-to-house survey for a period of one month.Materials and Methods:Two villages (Handiganur and Gundwad) were selected randomly from Belgaum and Raibag taluks of Belg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 3 publications
3
11
1
Order By: Relevance
“…This report is in line with previous findings elsewhere [6, 17, 23, 24, 26, 35, 36, 41, 42]. This might be due to a higher iodine requirement of females to support their growth and development [35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This report is in line with previous findings elsewhere [6, 17, 23, 24, 26, 35, 36, 41, 42]. This might be due to a higher iodine requirement of females to support their growth and development [35].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, about 57 % children had low urine iodine level (<100 ug/l) suggesting the presence of ID. This prevalence was in agreement with the report from South Tajiksitan (51.2 %) [36]. The difference in the median urinary iodine level between the current and the former study settings might be related to poor dietary intake of iodine rich food and low utilization of iodized salt in the study area.…”
Section: Discussionsupporting
confidence: 92%
“…[ 2 ] Surveys conducted in various states showed that no state in the country is free from IDD. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…3 Enlargement of thyroid gland is the common manifestation of iodine deficiency. 4 Schoolchildren (6 to 12 years) are the most vulnerable group to iodine deficiency. 5 Its manifestations can range from minor neurological changes, to impaired learning ability and underperformance in school.…”
Section: Introductionmentioning
confidence: 99%